Reflection of applying the requirement of IFRS 9 regards impairment of Banks loans on earning management in Iraqi Banks - عبد الله, بشرى نجم; عبد محمد, احمد جاسم (Journal of Economics and Administrative Sciences, 2018)
Impairment of financial assets defined according to IFRS 9 as the difference between all contractual cash flows that are due to an entity in accordance with the contract and all the cash flows that the entity expects to receive, the entity should estimates all the cash flows through looking to the contract terms during the life time period of the assets or for shorter period if possible, the cash flow should include the amounts of selling any collateral taken or any other enhancement. On the other hand, the Central bank of Iraq guidelines regards impairment differ from the IFRS 9 that’s does not consider the collateral value on calculating the impairment that’s effects on the net profit through recognizing exaggerated loss and at the same time indicator to earning management.This research aimed to present and analysis the requirement of IFRS 9 regards impairment, in addition to implement these requirement and show its effect on earnings management of sample of Iraqi listed private banks using loan loss provision model.The research had several findings; the most important is decrease the earning management practice for the sample of Iraqi listed private banks after implementing IFRS 9 regards impairment. Also, the research had suggest several recommendations, the most important is urged the officials at the Central bank of Iraq and those whom preparing the laws, instructions and guidelines the necessity of amendment the guidelines that currently in use to be reconciled with the requirements of IFRS 9 (financial instruments) and harmony with the Iraq environment for these standards, in addition to, provide the required requirement.